In Calculus, we learn that the slope of a tangent line to any point ( x , y ) on a parabola in the form of y = x 2 + b x + c is defined by its derivative y ′ = 2 x + b .
If the x-intercept of a tangent line of any point ( x , y ) on a certain parabola in the form of y = x 2 + b x + c can be defined by the equation 2 1 x − 3 , find b + c .
(For example, the x-intercept of the tangent line of this parabola at x = 1 is 2 1 ( 1 ) − 3 = − 2 5 , the x-intercept of the tangent line of this parabola at x = 2 is 2 1 ( 2 ) − 3 = − 2 , the x-intercept of the tangent line of this parabola at x = 3 is 2 1 ( 3 ) − 3 = − 2 3 , and so on.)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great solution! You have a small typo: x^2 - c = x^2 + (1/2b - 6) - 3b is missing an x and should be x^2 - c = x^2 + (1/2b - 6)x - 3b.
Since a line has an equation y = y ′ x + y 0 , where y ′ is the slope and y 0 is the y -intercept, the y -intercept is y 0 = y − y ′ x .
The x -intercept x 0 is the x value of y = y ′ x + y 0 when y = 0 , so 0 = y ′ x 0 + y 0 which rearranges to x 0 = y ′ − y 0 . Substituting y 0 = y − y ′ x and simplifying gives x 0 = x − y ′ y .
Now we have x 0 = x − y ′ y = 2 1 x − 3 , which rearranges to y y ′ = x + 6 2 or y 1 d y = x + 6 2 d x . Solving this differential equation gives ln ∣ y ∣ = 2 ln ∣ x + 6 ∣ + C for some constant C . Letting C = ln k , this solves to y = ± k ( x + 6 ) 2 or y = ± k ( x 2 + 1 2 x + 3 6 ) .
Since the x 2 term must have a coefficient of 1 , ± k = 1 , and so y = x 2 + 1 2 x + 3 6 , which means b = 1 2 and c = 3 6 , and b + c = 1 2 + 3 6 = 4 8 .
Problem Loading...
Note Loading...
Set Loading...
This problem can be solved using surprisingly little calculus. First, construct the equation of the line tangent at x. To avoid confusion I will use x,y for the variables relating to the parabola equation, and X,Y for the variables of the line. Then, in point-slope form the line has equation Y − ( x 2 + b x + c ) = ( 2 x + b ) ( X − x ) . Rearranging this gives Y = ( 2 x + b ) X − x 2 + c . For the X intercept, set Y=0 and solve for X: X = 2 x + b x 2 − c . Now, set that equal to the provided formula, so we have 2 1 x − 3 = 2 x + b x 2 − c , or x 2 − c = x 2 + ( 2 1 b − 6 ) − 3 b . These polynomials are equal for all x, so 2 1 b − 6 = 0 and c = 3 b . Solving these reveals b = 1 2 , c = 3 6 , for a final answer of 48.